The Reading of the Butler: Kazuo Ishiguro’s The Remains of the Day - Bényei, Tamás (FOCUS: Papers in English Literary and Cultural Studies, 2024)
“It must be an awful job to be a butler anyway” (Powell 144). These, only partly hypocritical, sentiments are expressed by Erridge, the Communist aristocrat in Anthony Powell’s At Lady Molly’s. Erridge’s remark is meant as a comment on his butler’s spectacular, self-destructive alcoholism: Smith, in what looks almost like metaphysical despair, has returned to the etymological root of his occupation and taken to the bottle. In Powell, alcoholism usually indicates a general collapse of the self, a failure of the individual to identify with his role (as in the more prominent case of Charles Stringham). Erridge’s comment indicates that in Smith’s case alcoholism is somehow only to be expected, since there is an inherent difficulty in the identification demanded by butlerhood, a painful truncation, something that affects the self damagingly. Following the logic of Erridge’s comment, one might conclude that the difference between a butler’s real self and the identity he has to assume as a butler acts as a disruptive force in the economy of the self, finding some outlet in the excessive habit of alcoholism which can be considered as an attempt to step out of the confines of an externally imposed identity.